Consumer behaviour : applications in marketing - East, Robert; Jaywant Singh; Vanhuele, Man; Wright, Malcolm (Sage, 2017)
Extending beyond a basic psychological approach to Consumer Behaviour, this text provides a more empirical understanding of the subject to help students consider not just the individual but also the market environment